2013
DOI: 10.1182/blood-2012-07-443762
|View full text |Cite
|
Sign up to set email alerts
|

Higher bone marrow LGALS3 expression is an independent unfavorable prognostic factor for overall survival in patients with acute myeloid leukemia

Abstract: Key Points Bone marrow LGALS3 expression is associated with distinct clinical and biological features in patients with acute myeloid leukemia. Higher bone marrow LGALS3 expression is an independent poor prognostic factor for overall survival and may serve as a potential therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 48 publications
6
28
1
Order By: Relevance
“…In the multivariate analysis, we observed that galectin-3 expression, together with some traditional prognostic factors (tumor size, histologic grade) were independent risk factors in the prognosis of HCC patients. Similar findings have been reported in other malignancies [26-29]. …”
Section: Discussionsupporting
confidence: 91%
“…In the multivariate analysis, we observed that galectin-3 expression, together with some traditional prognostic factors (tumor size, histologic grade) were independent risk factors in the prognosis of HCC patients. Similar findings have been reported in other malignancies [26-29]. …”
Section: Discussionsupporting
confidence: 91%
“…have been shown to be prognostic for poor survival in many cancers including leukemia, lymphomas, breast cancer, and thyroid cancer but decreased levels of Galectin 3 appear to be detrimental to patients with chronic lymphoblastic leukemia (CLL) or prostate cancer (23,36,(54)(55)(56)(57). A possible explanation for this variance could involve the intra-cellular localization of Galectin 3 within the cancer cells as the molecule's function will vary depending on whether it is in the nucleus, cytoplasm, nucleus, or extracellular spaces for that matter (23).…”
Section: ) the Role Of Galectin 3 In Various Cancers Is Complex Asmentioning
confidence: 99%
“…LGALS3 has clinical relevance as a target in many cancers [20, 30, 31]. Cheng and colleagues reported that elevated LGALS3 was prognostic for poor survival in AML patients [31].…”
Section: Introductionmentioning
confidence: 99%